Alcohol and drug use among deaf and hard-of-hearing individuals: A secondary analysis of NHANES 2013–2014. Issue 3 (3rd July 2018) - Anderson, Melissa L.; Chang, Bei-Hung; Kini, Nisha
ABSTRACT: Background : Within the field of behavioral health research, one of the most understudied populations is the US deaf and hard-of-hearing (D/HH) population—a diverse group of individuals with hearing loss that have varied language and communication preferences, community affiliations, and sociocultural norms. Recent research identified concerning behavioral health disparities experienced by the D/HH population; yet, little research has been conducted to extend these findings to the topic of substance use disorder. Methods : To begin to fill this gap, the authors conducted a secondary analysis of data from the 2013–2014 administration of the National Health and Nutrition Examination Survey, comparing alcohol and drug use between participants based on their reported hearing status, i.e., D/HH or hearing. Results : Findings suggest that the overall lifetime prevalence of alcohol and drug use does not differ based on hearing status, and that D/HH and hearing adolescents begin using cannabis on a similar timeline. However, findings also revealed that D/HH respondents were more likely to have been regular cannabis users and heavy alcohol users than hearing respondents. In other words, when D/HH individuals use substances, they tend to be heavy users. Conclusions : These findings stress the importance of directing resources to the prevention and treatment of heavy alcohol use in the D/HH population, given that binge drinking is associated with a number of health problems and social consequences. Additionally, the continuation of this empirical work is rather urgent given recent legislative changes regarding cannabis use. D/HH individuals possess a number of risk factors for substance use disorder and, as such, may be more greatly impacted by these legislative changes than individuals from the general US population. It is imperative that this impact be captured by future research efforts in order to inform the development of prevention and intervention efforts for the traditionally underserved D/HH population.